Pengembangan Sistem Informasi Manajemen Rumah Sakit Modul Analisis Kuantitatif Rekam Medis Dengan Menggunakan Metode Rapid Application Development Di RSJD Dr. RM. Soedjarwadi Provinsi Jawa Tengah - Astri Ayu Prasetiyani (Indonesian Journal of Health Information Management, 2023)
Abstract This quantitative analysis process is done manually using spreadsheet media. The assembling officers take time in conducting the monthly recapitulation. This study aims to develop a hospital management information system with inpatient medical record quantitative analysis module. It uses the Rapid Application Development method. The type of this study is Research and Development. This study is coonducted at RSJD Dr. RM. Soedjarwadi in November 2022 until January 2023. The subjects of this study were two Assembly Officers and two Electronic Data Processing Officers. Meanwhile the object of this study is the Quantitative Analysis of Medical Records Spreadsheet. The data is collected by observation and unstructured interviews. Moreover, the researcher uses Rapid Application Deveopment Software in processing the data. It consists of three stages wich are Planning, Designing System, and Testing System. The Result shows that the system which is made within 50 days can successfully carried out the testing with the Black-Box method in accordance with the needs of Assembly Officers. Keywords : Quantitative Analysis, Medical Record, Rapid Application Development Literature : 20 (2014, 2022)